Development of an EORTC-8D Utility Algorithm for Sri Lanka. (April 2015) - Kularatna, Sanjeewa; Whitty, Jennifer A.; Johnson, Newell W.; Jayasinghe, Ruwan; Scuffham, Paul A.
Background. Currently there are no reported cancer-specific health state valuations in low- and middle-income countries using a validated preference-based measure. The EORTC-8D, a cancer-specific preference-based measure, has 81, 920 health states and is useful for economic evaluations in cancer care. The aim of this study was to develop a utility algorithm to value EORTC-8D health states using preferences derived from a representative population sample in Sri Lanka. Methods. The time-tradeoff method was used to elicit preferences from a general population sample of 780 in Sri Lanka. A block design of 85 health states, with a time horizon of 10 years, was used for the direct valuation. Data were analyzed using generalized least squares with random effects. All respondents with at least one logical inconsistency were excluded from the analysis. Results. After logical inconsistencies were excluded, 4520 observations were available from 717 respondents for the analysis. The preferred model specified main effects with an interaction term for any level 4 or worse descriptor within a health state. Worsening of physical functioning had a substantially greater utility decrement than any other dimension in this population. Limitations are that the data collection could not include the whole country and that females formed a large part of the sample. Conclusions. Preference weights for EORTC-8D health states for Sri Lanka have been derived: These will be very useful in economic evaluations of cancer-related interventions in a range of low- and middle-income countries.